Suitability of Modified Coconut Copra and Groundnut Shell Based Soil Conditioner in Promoting Plant Growth of Abelmoschus esculentus - Haziqah, Hussein (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study was prepared to detennine the effectiveness of modified coconut copra and groundnut shell with humic acid as soil conditioner on promoting the plant growth. The study is conducted at the green house of University Malaysia Sarawak by using the plant commonly known as okra (Abelm(1schus esculentus) as tested plant. The data was obtained from the observation of germination stages of seed until its mature stage for a period of 10 weeks. For the first experiment, there are six treatments for each material; top soil only, top soil with fertilizer, raw coconut copra, and raw coconut copra with fertilizer, modified coconut copra and modified coconut copra with fertilizer. For the second experiment, there are six treatments for each material; top soil only, top soil with fertilizer, raw groundnut shell, raw ground nut shell with fertilizer, modified groundnut shell and modified groundnut shell with fertilizer. Those treatments that involved with the usage of fertilizers had the same amount of Sg for each pot. The parameters used for this assessment are the height of the plant, the stem diameter, total number of leaves, root to shoot ratio and the nutrient deficiency. The measurement of plant growth was taken once in every two week. The results from this study shows that treatment of modified coconut copra as soil conditioner in addition of fertilizer shows stunted growth while treatment of modified groundnut shell as soil conditioner in addition of fertilizer gives positive response towards plant growth of Abelmoschus esculentus.